Progress towards a best practice method for modelling dispersion of bioaerosols from composting facilities - Drew, Gillian H.; Tamer Vestlund, Asli; Jordinson, Greg M.; Taha, Mohd Pauze M.; Smith, Richard; Tyrrel, Sean F.; Longhurst, Philip J.; Pollard, Simon J. T. (Cranfield University, 2007)
The promotion of composting in the UK as a sustainable waste management option has led to concerns regarding exposure of the public to potentially harmful emissions of airborne micro-organisms or bioaerosols. In response to public concerns, the Environment Agency in England and Wales requires a risk assessment for any licensed composting facility that has a sensitive receptor within 250m of the site boundary. An ongoing programme of studies in association with the Environment Agency has begun to explore methods to improve exposure assessments for bioaerosols. Our results have shown that is is possible to use air dispersion models for estimating downwind concentrations of bioaerosols, and the more advanced modelling options, such as the use of intermittent emission rates, result in lower downwind concentrations. Current risk assessments may be over-estimating the exposure of receptors to bioaerosols from composting, however further studies are needed to validate the results presented here. 1. INTRODUCTION The promotion of composting in the UK as a more sustainable waste management option has led to concerns regarding exposure of the public to potentially harmful emissions of airborne microorganisms or bioaerosols. The composting process is reliant on various micro-organisms, such as bacteria and fungi, to break down the organic matter. However, if as a result of composting operations these micro-organisms become airborne, may be breathed in, and due to their small size, can penetrate deep into the human respiratory system. Conditions such as farmer's lung disease and aspergillosis (Latgé, 1999) have been linked to high concentrations of bioaerosols, although dose-response relationships are not well defined. In response to public concerns, the Environment Agency in England and Wales requires a risk assessment for any licensed composting facility that has a sensitive receptor within 250m of the